Colorimetric detection of nitrogen, phosphorus, and potassium contents and integration into field irrigation decision technology. Issue 4 (February 2021) - Liu, Na; Wei, Zhengying; Wei, Haoran
Abstract: In order to precisely provide nitrogen, potassium, and phosphorus via irrigation, this study designed a method for their field detection based on photoelectric colorimetry. We determined the maximum UV-vis absorption wavelengths of nitrogen, phosphorus, and potassium solutions mixed with colorimetric reagents and experimentally determined their standard curves. The detection error was less than 5% by error analysis, and thus the method can be used to determine the concentrations of the target elements on site. We also combined the detection of potassium, nitrogen, and phosphorus with intelligent irrigation decision-making to achieve automatic irrigation. The accurate technology that we developed for controlling water-soluble fertilizers can detect the target elements on-site, which improves the controlled performance of accurate irrigation systems through fast and efficient on-site detection.